Peningkatan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Discovery Learning berbantuan Media Audio Visual Fase D SMPN 10 Surakarta - Andre Tri Prihatin (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The implementation of the Merdeka Curriculum in Catholic Religious Education Lessons at SMP Negeri 10 Surakarta shows a decline in student learning outcomes. These obstacles are related to the lack of adaptation of learning methods and teacher innovation in adopting curriculum changes, which has an impact on learning which tends to be teacher-centred. To overcome this problem, classroom action research was conducted by applying the discovery learning model and audio-visual assistance in phase D. This research, through two face-to-face cycles, showed a significant increase in students' cognitive and affective learning outcomes. In the cognitive aspect, there was an increase in understanding of the material from 55.5% in cycle I to 66.6% in cycle II. There were no students belonging to the newly developing category in both cycles. Meanwhile, affective learning results showed an increase in students' devout attitudes from 33.3% in cycle I to 66.6% in cycle II. Thus, it can be concluded that the application of the discovery learning model with audio visual assistance is effective in improving learning outcomes and students' devotion to Catholic Religious Education material at SMP Negeri 10 Surakarta.